2022
DOI: 10.3390/genes13061054
|View full text |Cite
|
Sign up to set email alerts
|

Old and New Systemic Immune-Inflammation Indexes Are Associated with Overall Survival of Glioblastoma Patients Treated with Radio-Chemotherapy

Abstract: Background. Systemic immunity and inflammation indexes (SI) derived from blood cells have gained increasing attention in clinical oncology as potential biomarkers that are associated with survival. Materials and methods. We tested 12 different SI using blood tests from patients with isocitrate dehydrogenase 1 and 2 wild-type glioblastomas, treated with radio-chemotherapy. The primary endpoint was their overall survival. Results. A total of 77 patients, comprising 43 males and 34 females, with a median age of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Current approaches in immunotherapy, e.g., by personalized peptide vaccination, can lead to an increased infiltration of CD8-positive T cells and increased immunogenicity [ 65 ]. Moreover, systemic immunosuppressive and inflammation markers can be influenced by novel therapeutic options as well [ 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current approaches in immunotherapy, e.g., by personalized peptide vaccination, can lead to an increased infiltration of CD8-positive T cells and increased immunogenicity [ 65 ]. Moreover, systemic immunosuppressive and inflammation markers can be influenced by novel therapeutic options as well [ 66 , 67 , 68 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…This pain sensitivity modulation is another possible mechanism. Also, the headache may be aggravated or modified by promoting systemic inflammation due to GBM [10], which is related to GBM prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Duplicate studies were excluded, and conference abstracts or studies lacking sufficient data were excluded after full-text evaluation. Five studies that enrolled 788 patients were included in the final metaanalysis [20][21][22][23]26]. The selection process of the meta-analysis is shown in Supplementary Figure S1.…”
Section: A Meta-analysis Evaluating the Prognosis Of Sii In Patients ...mentioning
confidence: 99%
“…The systemic immune-inflammation index (SII) [17], a novel inflammatory biomarker calculated by platelet count*neutrophil count/lymphocyte count, has been determined to be related to worse outcomes in many cancer patients, including breast cancer [18], hepatocellular carcinoma [19] and glioma [20]. Two recent studies reported that a higher SII was associated with a worse outcome in the GBM cohort [21,22]. However, the prognostic value of the SII is still controversial.…”
Section: Introductionmentioning
confidence: 99%